BIODIESEL DENGAN ALTERNATIF BAHAN BAKU MINYAK NABATI BARU DAN BEKAS - Kusumayanti, Heny; Puspitasari, Nurul (Universitas Diponegoro, 2007)
Abstract Biodiesel represent one of substance of alternative of fuel substitution which can be innovated and friendly environmentally. This Biodiesel earn also made plainly Â and Â exploit the existing substance around. Price from raw material its maker also cheap enough. The example by using new vegetation oil and ex-vegetation oil. Process of with the process transesterifikasi, that is dissolve the oil by NaOH and methanol. Later then mingled and yield two coat after hushed 8 clock that is flake is biodiesel and substratum is gliserol. Examination conducted by experience is combustion by using tinder and with the iron rasher Keywords : biodiesel, oil